Viable justice: survivors of sexual and gender-based violence and/or torture amongst South Sudanese refugees living in settlements in Northern Uganda - Liebling, Helen Jane; Barrett, Hazel Rose; Artz, Lillian; Shahid, Ayesha (International journal of migration, health and social care, 2024)
Purpose The study aimed to listen to refugee survivors of sexual and gender-based violence (SGBV) and/or torture and explore what justice meant to them in exile. This study argues that what the survivors who participated in this research wanted was “viable justice”. The research was funded by the British Academy and Leverhulme Trust. Design/methodology/approach Using a survivor-focussed justice lens combined with a trauma-informed approach, narrative interviews were held with 41 women and 20 men refugee survivors living in refugee settlements in Northern Uganda. The researchers also conducted semi-structured interviews with 37 key informants including refugee welfare councils, the UN, civil society, non-government and government organisations. Thematic analysis of the data resulted in the following themes being identified: no hope of formal justice for atrocities that occurred in South Sudan; insecurity; lack of confidence in transitional justice processes in Ugandan refugee settlements; abuse and loss of freedom in refugee settlements; and lack of access to health and justice services in refugee settlements. Findings This study argues that what the survivors who participated in this research wanted was “viable justice”. That is justice that is survivor-centred and includes elements of traditional and transitional justice, underpinned by social justice. By including the voices of both men and women survivors of SGBV and/or torture and getting the views of service providers and other stakeholders, this paper offers an alternative form of justice to the internationally accepted types of justice, which offer little relevance or restitution to refugees, particularly where the crime has been committed in a different country and where there is little chance that perpetrators will be prosecuted in a formal court of law. Research limitations/implications The research findings are based on a small sample of South Sudanese refugees living in three refugee settlements in Northern Uganda. Thus, wider conclusions should not be drawn. However, the research does suggest that a “viable justice” approach should be implemented that is gender and culturally sensitive and which could also be trialled in different refugee contexts. Practical implications Improvements in refugee survivors’ dignity, resilience and recovery are dependent upon the active engagement of refugees themselves using a “survivor-focussed approach” which combines formal and community-based health services with traditional and transitional justice responses. Social implications The provision of a “viable justice approach” ensures those who have experienced SGBV and/or torture, and their families, feel validated. It will assist them to use their internal, cultural and traditional resilience and agency in the process of recovery. Originality/value The research findings are original in that data was collected from men and women survivors of SGBV and/or torture and service providers. The empirical evidence supports this study’s recommendation for an approach that combines both formal and survivor-focussed approaches towards health and viable justice services to meet the needs of refugees living in refugee settlements. This is a response that listens to and responds to the needs of refugee survivors in a way that continues to build their resilience and agency and restores their dignity.